PENGEMBANGAN MEDIA PERKALIAN BILANGAN CACAH BERBASIS NEARPOD KELAS 4 SEKOLAH DASAR - Dhiya Puspa Sari; Sri Rahayu, Nyamik Rahayu Sesanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning in one of the Elementary Schools in Malang City still faces various challenges, one of which is the use of concrete media in the form of dominoes in learning multiplication of whole numbers in grade 4. This development research aims to determine the feasibility, practicality and effectiveness of Nearpod-based learning media in mathematics learning. This development research uses a Research and Development (R&D) research design that refers to the ADDIE development model with 5 stages, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. This research passed a feasibility test from media experts, material experts and language experts. The subjects of this research involved teachers and grade 4 students, through two trial stages: a limited field involving 3 students and a wide field involving 25 students. Data were analyzed based on validation sheet instruments, questionnaires and tests to assess improvements in student learning outcomes. The feasibility results by media experts obtained a percentage of 95.4%, material experts obtained a percentage of 92.5% and language experts obtained a percentage of 96.8%, the feasibility of Nearpod-based learning media obtained an average of 94.9% included in the